Experiment and numerical simulation of a full-scale helicopter composite cockpit structure subject to a bird strike - Hu, Dayong; Song, Bin; Wang, Dongfang; Chen, Zuyong (Composite structures, 2016)
Bird strike is one of the most critical safety issues in aviation, which usually leads to catastrophic casualties. In this paper, an effective FE–SPH coupling model is developed to investigate the structure crashworthiness performance of a helicopter composite cockpit (HCC) subject to a bird strike by using an explicit nonlinear finite element code ANSYS/LS-DYNA 3D. The mechanical parameters of the bird constitutive model are obtained by a bird strike test on flat plate and the validated bird model is subsequently implemented to simulate a bird striking on HCC according to Federal Aviation Regulation 29.631. A full-scale HCC bird strike experiment is also performed under the same impact condition to certify airworthiness requirement as well as validate the FE model. The high agreement between the experiment and numerical analysis builds confidence in future use of FE method as a predictive tool. Based on numerical results, a structure design modification is also performed to enhance the structure stiffness and improve bird strike resistance.